CD4+Foxp3+T Regulatory Cells Promote Transplantation Tolerance by Modulating Effector CD4+ T Cells in a Neuropilin-1-Dependent Manner - Campos-Mora, Mauricio; Contreras-Kallens, Pamina; Gálvez-Jirón, Felipe; Rojas, Masyelly; Rojas, Carolina; Refisch, Aarón; Cerda, Oscar; Pino-Lagos, Karina (Frontiers in Immunology, 2019)
Several mechanisms of immune suppression have been attributed to Foxp3+ T regulatory cells (Treg) including modulation of target cells via inhibition of cell proliferation, alteration of cytokine secretion, and modification of cell phenotype, among others. Neuropilin-1 (Nrp1), a co-receptor protein highly expressed on Treg cells has been involved in tolerance-mediated responses, driving tumor growth, and transplant acceptance. Here, we extend our previous findings showing that, despite expressing Foxp3, Nrp1KO Treg cells have deficient suppressive function in vitro in a contact-independent manner. In vivo, the presence of Nrp1 on Treg cells is required for driving long-term transplant tolerance. Interestingly, Nrp1 expression on Treg cells was also necessary for conventional CD4+ T cells (convT) to become Nrp1+Eos+ T cells in vivo. Furthermore, adoptive transfer experiments showed that the disruption of Nrp1 expression on Treg cells not only reduced IL-10 production on Treg cells, but also increased the frequency of IFN+ Treg cells. Similarly, the presence of Nrp1KO Treg cells facilitated the occurrence of IFN+CD4+ T cells. Interestingly, we proved that Nrp1KO Treg cells are also defective in IL-10 production, which correlates with deficient Nrp1 upregulation by convT cells. Altogether, these findings demonstrate the direct role of Nrp1 on Treg cells during the induction of transplantation tolerance, impacting indirectly the phenotype and function of conventional CD4+ T cells.